Hemothorax Caused by Liver Biopsy – Rare Iatrogenic Complication - Samiatina-Morkūnienė, Diana; Silickytė, Rūta; Jankauskaitė, Gabija (Lietuvos chirurgija, 2023)
Liver biopsy is the most accurate interventional procedure to diagnose hepatic diseases. According to the information provided by the Institute of Hygiene, 968 percutaneous liver biopsies were performed in Lithuania in 2022. The Lithuanian scientific literature does not, however, publish information on complications associated with this procedure. According to international literature, the frequency of complications after this procedure ranges from 2.4% to 9.5%. The most common are mild complications: hematomas, fever, pain at the biopsy site. Particularly rare are hemothorax, pneumothorax, damage to the organs of the thoracic and abdominal cavity, which occur in up to 0.04% of cases. This article presents an extremely rare complication – liver biopsy induced hemothorax, whose success was determined by early diagnosis and timely surgical intervention.